Sleep and Gastrointestinal Symptoms in a Community-based Survey of Children - Jansen, Erica C. (Clin Pediatr (Phila), 2018)
We examined whether gastrointestinal (GI) symptoms were associated with sleep disturbances in a community-based sample of 337 school-age children from Ypsilanti, Michigan. Parents completed the sleep-related breathing disorder (SRBD) scale of the Pediatric Sleep Questionnaire and the Conners’ parents rating scale, which included questions concerning GI symptoms. One-fifth of the children screened positive for SDB; the same fraction had sleepiness, and one-quarter snored more than half the time. Similarly, one-quarter of children had two or more GI symptoms. Children with positive SDB scores were 2.22 times as likely to have two or more GI symptoms in the past month after confounder adjustment (95% CI 1.39–3.55). In particular, this relationship appeared to be driven by daytime sleepiness, as children with sleepiness had about a 2-fold higher prevalence of two or more GI symptoms (adjusted prevalence ratio= 1.96, 95% CI 1.18–3.26). Neither snoring nor sleep duration were associated with GI symptoms.